An all-aqueous redox flow battery with unprecedented energy density. Issue 8 (20th June 2018) - Zhang, Jing; Jiang, Gaopeng; Xu, Pan; Ghorbani Kashkooli, Ali; Mousavi, Mahboubeh; Yu, Aiping; Chen, Zhongwei
Abstract : A hybrid alkaline zinc–iodine redox flow battery has been designed with an unprecedented energy density record to date for an all-aqueous redox flow battery. Abstract : Redox flow batteries are of particular interest because of the flexible power and energy storage originating from their unique architecture, but their low energy density has inhibited their widespread dissemination. In this work, a novel strategy of tuning the pH of the electrolyte environment is put forward to enhance the battery voltage, and eventually achieve the goal of high energy density for all-aqueous redox flow batteries. With this strategy, a hybrid alkaline zinc–iodine redox flow battery has been designed with a 0.47 V potential enhancement by switching the anolyte from acidic to basic, thus inspiring an experimental high energy density of 330.5 W h L −1 . This is an unprecedented record to date for an all-aqueous redox flow battery.